Characterization of mechanical properties of two-dimensional materials mounted on soft substrate. (February 2019) - Liu, Yanwei; Wei, Yueguang; Chen, Pu
Highlights: A theoretical indentation model applicable to film/substrate systems with large modulus ratios (Ef /Es  = 10 2 –10 5 ) is established. A new convenient method for measuring the modulus of nanofilm with limited thickness by indentation on hard film/soft substrate system is proposed. Compared with the free-standing indentation test or bulge test, this method is more convenient and cheaper. The effectiveness of the model and method was verified by experiments and simulations. Abstract: Two-dimensional (2D) materials have received extensive attention due to their excellent physical and chemical properties, whose mechanical properties play critical roles in their applications. In this paper, a new convenient method for measuring the modulus of nanofilm by indentation on hard film/soft substrate system is proposed. In order to verify the correctness of the new method, the graphene oxide (GO) nanofilm deposited on polydimethylsiloxane (PDMS) is tested. The modulus of the GO nanofilm is measured as 60.39 ± 7.82 GPa, which is consistent with the modulus measured by previous researches. Finally, the finite element method (FEM) is used to investigate the effectiveness of the new method and to evaluate its error sensitivity to the indenter size, film radius, and the surface roughness. The results show that this method can accurately measure the modulus of nanofilm through the indentation response of the hard film/soft substrate system. Compared with the free-standing indentation test, the method proposed by us eliminates the disadvantages of boundary adhesion and has the advantages of simple sample preparation, easy operation, and high success rate.